Combating Malaria Through E-SISMAL: How Perceived Quality, Perceived Ease of Use, and Perceived Usefulness Impact Performance? A Case of West Papua Province - Chandra Leonard Kandami; Dedi I. Inan; Ratna Juita; Muhammad Indra (Faculty of Computer Science Universitas Indonesia, 2025)
Malaria remains a serious health threat in Indonesia, particularly in the West Papua Province. To address this, the Indonesian Ministry of Health developed the Malaria Surveillance Information System (E-SISMAL) to monitor and prevent the disease. However, the effectiveness of this system needs to be evaluated to determine how well it performs in addressing the intended problem. This study aims to investigate the system’s performance by integrating the Task-Technology Fit (TTF), Technology Acceptance Model (TAM), and DeLone & McLean Information Systems (D&M IS) Success models. Data from 108 government health clinics in West Papua Province were collected using questionnaires and analyzed using a partial least squares structural equation model (PLS-SEM). The findings revealed that both service quality (p = 0.035) and ease of use (p = 0.014) significantly influenced user satisfaction (R² = 38.4%), which subsequently affected system performance (p < 0.000, R² = 11.6%). However, information quality and usefulness were not primary concerns for the health clinics in this context. Given these results, it is unsurprising that malaria prevention efforts in this region remain challenging. These findings raise questions about the alignment of the developed system with its objectives, suggesting that it may need reassessment and reconfiguration to achieve its overarching goals. The study concludes with implications and future research directions.